Cooperation or democratisation? The EU'S conflicting Mediterranean security discourses - Helle Malmvig (Danish Institute for International Studies (DIIS), 2004)
This paper argues that the EU's strategy towards the Southern Mediterranean states has been marked by a simultaneous presence of two conflicting and mutually incompatible security discourses. Each of these discourses entail different conceptualisations of how security is to be achieved, who is the referent object of security, and which type of relationship exists between Self/the EU and Other/the Southern Mediterranean. This, the paper suggests, has resulted in an uneasy and contradictory EU policy toward the region, while at the same time causing suspicion and mistrust on part of the Mediterranean states.
Keywords: 330